Application of multistage Artificial Immune System for optimal network reconfiguration in distribution system / Mohamad Fuad Mohd. Ishak - Mohd. Ishak, Mohamad Fuad (2007)
A power distribution system normally is designed as weakly meshed network but the sytem is operated as radial because of protective problem. To make the system radial, Severak sectionalizing switches of the network must be opened.